2003
DOI: 10.1196/annals.1284.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unilateral Temporal Lobe Resection on Short‐Term Memory for Auditory Object and Sound Location

Abstract: To investigate auditory spatial and nonspatial short-term memory, a sound location discrimination task and an auditory object discrimination task were used in patients with medial temporal lobe resection. The results showed a double dissociation between the side of the medial temporal lobe lesion and the nature of the auditory discrimination deficits, suggesting that right and left temporal lobe structures are differently involved in auditory spatial and nonspatial short-term memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Human neuroimaging studies have reported activation of MTL during working memory (WM) tasks that engage informational encoding (Campo et al 2005; Karlsgodt et al 2005; Mainy et al 2007), maintenance of information (Ranganath and D'Esposito 2001; Axmacher et al 2007), and retrieval (Cabeza et al 2002; Schon et al 2009). Also supporting this view, neuropsychological and neuroimaging studies have revealed impaired performance and abnormalities in MTL activity during WM tasks in patients with MTL damage with various causes (Owen et al 1996; Krauss et al 1997; Abrahams et al 1999; Grady et al 2001; Lancelot et al 2003; Lee et al 2006; Olson et al 2006; Piekema et al 2007; Ezzyat and Olson 2008; Wagner et al 2009). However, based on the assumption that cognitive processes engage distributed neural networks, if we want to gain a clearer understanding of the functional role of MTL in WM it cannot be considered as an independent processor.…”
Section: Introductionmentioning
confidence: 75%
“…Human neuroimaging studies have reported activation of MTL during working memory (WM) tasks that engage informational encoding (Campo et al 2005; Karlsgodt et al 2005; Mainy et al 2007), maintenance of information (Ranganath and D'Esposito 2001; Axmacher et al 2007), and retrieval (Cabeza et al 2002; Schon et al 2009). Also supporting this view, neuropsychological and neuroimaging studies have revealed impaired performance and abnormalities in MTL activity during WM tasks in patients with MTL damage with various causes (Owen et al 1996; Krauss et al 1997; Abrahams et al 1999; Grady et al 2001; Lancelot et al 2003; Lee et al 2006; Olson et al 2006; Piekema et al 2007; Ezzyat and Olson 2008; Wagner et al 2009). However, based on the assumption that cognitive processes engage distributed neural networks, if we want to gain a clearer understanding of the functional role of MTL in WM it cannot be considered as an independent processor.…”
Section: Introductionmentioning
confidence: 75%
“…These studies found that TLE patients after ATL present no deficit in a simple pitch discrimination task (Johnsrude et al, 2000), but impairments in short-term memorisation of harmonic sound pitch (Zatorre and Samson, 1991) and of bird songs (Lancelot et al, 2003). Our results after ATL are consistent with these previous works, but since we already observed similar deficits in TLE patients before surgery, our findings further suggest that auditory deficits observed in TLE patients after ATL are most likely due to the epilepsy itself than to the brain resection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pinek et al (1989) reported that sound lateralisation deficits occur in both hemifields, especially after left hemisphere damage; in contrast, (Ruff et al, 1981) stated that deficits occur primarily after right hemisphere damage. These and similar diverse findings in the literature may be attributed to localisation of the individual lesions in different cortical regions such as temporal (Clarke et al, 2000) or parietal lobes (Griffiths et al, 1998), and to differences in experimental paradigms that may involve auditory short-term memory (Lancelot et al, 2003) or psychophysical explorations (Griffiths et al, 1997), as well as to differences in imaging techniques employed, such as magnetic resonance imaging (Zatorre and Penhune, 2001) and positron emission tomography (Weeks et al, 1999).…”
Section: Introductionmentioning
confidence: 63%